Pengaruh Jenis Usaha Dan Modal Terhadap Pendapatan Pedagang Di Pasar Sentral Kabupaten Mamuju - Aswar, Aswar; Heryati, Yati; Saputra A, Jeffriansyah Dwi (Fakultas Ekonomi & Bisnis Universitas Muslim Indonesia, 2025)
This study aims to determine how business type and capital influence the income of traders in the Central Market of Mamuju Regency. The research method used is quantitative, with primary data collected using a questionnaire. The respondent population was all traders in the Central Market of Mamuju Regency, and a sample of 30 traders was taken. This research method used multiple linear regression, validity tests, reliability tests, partial tests (t-tests), and f-tests. The results show that the variable Business Type has a partial significant effect on Trader Income in Mamuju Regency, with a significance value of 0.007, less than 0.05. The variable Capital has a partial significant effect on Trader Income in Mamuju Regency, with a significance value of 0.003, less than 0.05. The variables Business Type and Capital simultaneously have a significant effect on Trader Income in Mamuju Regency, with a significance value of 0.000, less than 0.05.